Lyapunov-Type Inequalities for Some Quasilinear Dynamic System Involving the (p1,p2,…,pm)-Laplacian on Time Scales - Xiaofei He; Qi-Ming Zhang (Journal of Applied Mathematics)
We establish several new Lyapunov-type inequalities for some quasilinear dynamic system involving the (p1,p2,…,pm)-Laplacian on an arbitrary time scale 𝕋, which generalize and improve some related existing results including the continuous and discrete cases.